Effectiveness of PBL Models Assisted by Interactive Video on Problem-Solving Abilities of Elementary School Students (Universitas Negeri Semarang, 2019)
The purpose of this study was to analyze the effectiveness of PBL models assisted by interactive videos on students' problem-solving abilities. The type of research used was quantitative research with the design of the control group pre-test post-test. The study population consisted of all fourth-grade students in the Kartini Group of Kudus City. The sample was selected through a purposive sampling technique so that the fourth grade of Elementary School Glantengan was selected which amounted to 27 students as the experimental group and fourth-grade Elementary School 4 Panjunan which amounted to 29 students as the control group. Data collection techniques use test techniques. The results of this study indicate that the classical completeness of the problem-solving ability of the experimental class reaches 92.5% with an average value of 83.52. The results of the analysis of problem-solving abilities in the experimental class showed that the indicator of understanding the problem had increased from 54% to 83%. The indicator for planning has increased from 56% to 82%. The indicator of solving problems has increased from 59% to 80%. The checking indicator has increased from 58% to 81%. The experimental class N-gain score scores reached 0.62 with a moderate category.